Avaliação da influência dos programas Universidade Aberta da Terceira Idade e Revitalização Geriátrica sobre a qualidade de vida de idosos - Castro, Paula Costa (Universidade Federal de São Carlos, 2007)
There was evaluated the influence on quality of life and its physical parameters correlation of the elderly during the first term of São Carlos Open University of the Third Age (named UATI) and Geriatric Revitalization Program (REVT). Participants - 135 individuals of first year at UATI and Geriatric Revitalization Program with mean age of 63,83 (±7,22) years. The volunteers were evaluated on physical measures (balance, body flexibility, muscle strength, aerobic capacity, blood pressure, weight, height and heart rate), besides aswering the the SF36 and WHOQOL-bref quality of life questionaries and happyness enterview on the beginning and after four months intervention. The UATI intervention concerns physical activities, including physical therapy group, art, culture and leisure. The REVT had 48 physical activity sessions, 16-week period, three times a week, lasting 50-55 minutes each. The data were analyzed using ANOVA with repeated measurements. There were no differences between the two groups. Both groups showed significant increase on quality of life level according the overall result WHOQOL bref; on Psychological domain, Environment domain, Question 1 and Question 2 of WHOQOL bref; and General Health of SF36. The Physical and Social domains of WHOQOL bref and other domains of SF36 do not showed significant improvement. Between physical measures, both groups showed improvement on body flexibility, balance, maximal oxygen uptake and blood pressure. There was no differences on muscle strength, weight, height and heart rate. There was weak and most times no significant correlation among physical measures and quality of life questionary domains. There was also weak correlation (or no correlation) between similar domains of WHOQOL-bref and SF36, indicating difference between the measures. The WHOQOL-bref showed better sensivity for this study sample. These programs contributed to increase quality of life according to WHOQOL - bref.
Keywords: Geriatria; Fisioterapia; Idosos; Programa de intervenção; Qualidade de vida; Saúde coletiva; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL